Changes in composition and enamel demineralization inhibition activities of gallic acid at different pH values. (November 2015) - Zhang, Jingyang; Huang, Xuelian; Huang, Shengbin; Deng, Meng; Xie, XINCHENG; Liu, Mingdong; Liu, Hongling; Zhou, Xuedong; Li, Jiyao; Ten Cate, Jacob Martien
Abstract: Background. Gallic acid (GA) has been shown to inhibit demineralization and enhance remineralization of enamel; however, GA solution is highly acidic. This study was to investigate the stability of GA solutions at various pH and to examine the resultant effects on enamel demineralization. Methods. The stability of GA in H2 O or in phosphate buffer at pH 5.5, pH 7.0 and pH 10.0 was evaluated qualitatively by ultraviolet absorption spectra and quantified by high performance liquid chromatography with diode array detection (HPLC-DAD). Then, bovine enamel blocks were subjected to a pH-cycling regime of 12 cycles. Each cycle included 5 min applications with one of the following treatments: 1 g/L NaF (positive control), 4 g/L GA in H2 O or buffered at pH 5.5, pH 7.0 and pH 10.0 and buffers without GA at the same pH (negative control), followed by a 60 min application with pH 5.0 acidic buffers and a 5 min application with neutral buffers. The acidic buffers were analysed for dissolved calcium. Results. GA was stable in pure water and acidic condition, but was unstable in neutral and alkaline conditions, in which ultraviolet spectra changed and HPLC-DAD analysis revealed that most of the GA was degraded. All the GA groups significantly inhibited demineralization ( p < 0.05) and there was no significant difference of the inhibition efficacy among different GA groups ( p > 0.05). Conclusions. GA could inhibit enamel demineralization and the inhibition effect is not influenced by pH. GA could be a useful source as an anti-cariogenic agent for broad practical application.